The vernacular in Anglo-Saxon charters: expansion and innovation in ninth-century England - Gallagher, R (Wiley, 2018)
This article offers a systematic analysis of the earliest uses in charters of the Anglo-Saxon vernacular, Old English, for purposes other than describing the geographic landscape. By doing so, the article draws attention to the dynamism of documentary culture in the first half of the ninth century and it argues that several of the developments of the period are best understood when considered from an international perspective. Adding nuance and detail to our view of ninth-century Anglo-Saxon literary activity, this investigation has significant implications for our understanding of early medieval literacy, language choice and uses of the written word.